Technological Change, Growth and Income Inequality - Wahiba, Nasfi Fkili; Dina, Mahmoudi (International Journal of Economics and Financial Issues, 2023)
This paper aims to demonstrate the links between inequality, economic growth and technological change. The latter combined with human capital distinguishes between skilled and unskilled workers which leads to rising inequality. Thus, we analyse the theoretical and empirical links between growth, technological change, school enrolment, openness, unemployment and income inequality. Therefore, the aim of this paper is to show that technological change is one of the key elements of economic growth and inequality dynamics. It is a channel through which human capital influences economic growth and also inequality. We are conducting an econometric study for a set of African countries in order to answer these questions: What is the impact of economic growth and technological change on inequality? What is the impact of income inequality on economic growth? What is the effect of openness and technological change on economic growth?